Evaluation and prediction of the level of high-quality development: A case study of the Yellow River Basin, China. (October 2021) - Jiang, Long; Zuo, Qiting; Ma, Junxia; Zhang, Zhizhuo
Highlights: Discussed the concept of high-quality development (HQD) systematically. 30 indicators were used to assess the level of HQD. Four HQD scenarios were simulated by using the system dynamics model. Results can guide the implementation of the Yellow River's major national strategy. Abstract: High-quality development (HQD) is the requirement for adapting to the changes in the main contradictions of Chinese society and achieving sustained and stable development. Based on the discussion of its connotation, this study constructed an evaluation model covering five aspects of society, economy, resources, ecology, and culture. Then we used the obstacle diagnosis model to analyze the main obstacle factors of restricting the improvement of HQD level. Finally, 4 future policy scenarios were designed under the system dynamics (SD) model to simulate the variation of the future development in each province along the Yellow River Basin (YRB). The results show that: (1) The level of HQD in the YRB changed dynamically over time, and it has also improved to varying degrees in all provinces. (2) The cultural subsystem hindered the further improvement of the HQD; for the indicator layer, the proportion of cultural industry in GDP is the main obstacle factor for most provinces. (3) Speeding up economic development and increasing ecological protection is the optimal development path of the YRB. Scientific evaluation of the regional HQD status and simulating the development situation under different scenarios can improve the accuracy and efficiency of managers' decision-making.